2020
DOI: 10.1186/s12887-020-02058-0
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare access and adverse family impact among U.S. children ages 0–5 years by prematurity status

Abstract: Background: Many children and their families are affected by premature birth. Yet, little is known about their healthcare access and adverse family impact during early childhood. This study aimed to (1) examine differences in healthcare access and adverse family impact among young children by prematurity status and (2) determine associations of healthcare access with adverse family impact among young children born prematurely. Methods: This was a secondary analysis of cross-sectional 2016 and 2017 National Sur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 48 publications
1
4
1
Order By: Relevance
“…Moreover, close examination of the data revealed that child chronic health condition(s)' interaction terms with family income at or below 100% of the FPL (OR = 0.09, p < 0.05) and family income at 101-200% of the FPL (OR = 4.37 × 10 −7 , p < 0.01) yielded strongly negative associations with child health, implying low-birth-weight children with chronic conditions in low-income families would have an escalated risk of poor/fair health. On the other hand, although the present study's finding on the insignificant impact of parent's employment status was contrary to the result of a prior study [27], another close examination of the data showed that the interaction term between parent employment and family income at 101-200% of the FPL (OR = 17.15, p < 0.05) had a strong positive association with low-birth-weight children's likelihood of "excellent/very good/good" health. In other words, parent's full employment did help low-birth-weight children gain good health among many low-income families.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Moreover, close examination of the data revealed that child chronic health condition(s)' interaction terms with family income at or below 100% of the FPL (OR = 0.09, p < 0.05) and family income at 101-200% of the FPL (OR = 4.37 × 10 −7 , p < 0.01) yielded strongly negative associations with child health, implying low-birth-weight children with chronic conditions in low-income families would have an escalated risk of poor/fair health. On the other hand, although the present study's finding on the insignificant impact of parent's employment status was contrary to the result of a prior study [27], another close examination of the data showed that the interaction term between parent employment and family income at 101-200% of the FPL (OR = 17.15, p < 0.05) had a strong positive association with low-birth-weight children's likelihood of "excellent/very good/good" health. In other words, parent's full employment did help low-birth-weight children gain good health among many low-income families.…”
Section: Discussioncontrasting
confidence: 99%
“…While this study found low-birth-weight children who were Black to be 95% less likely than low-birth-weight White children to have "excellent/very good/good" health, other low-birth-weight children from racial/ethnic minorities had no significant health difference with low-birth-weight White children. Moreover, consistent with the results of a prior study [27], the present study demonstrated that parents' low education and having a family income at or below 100% of the FPL significantly reduced low-birth-weight children's likelihood of "excellent/very good/good" health. Moreover, close examination of the data revealed that child chronic health condition(s)' interaction terms with family income at or below 100% of the FPL (OR = 0.09, p < 0.05) and family income at 101-200% of the FPL (OR = 4.37 × 10 −7 , p < 0.01) yielded strongly negative associations with child health, implying low-birth-weight children with chronic conditions in low-income families would have an escalated risk of poor/fair health.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations